An Experimental Study on the Water-Induced Strength Reduction in Zigong Argillaceous Siltstone with Different Degree of Weathering - Yu-chuan Yang; Jia-wen Zhou; Fu-gang Xu; Hui-ge Xing (Advances in Materials Science and Engineering)
The water-softening property of soft rocks is a key problem in geotechnical engineering. A typical red-bed soft rock (the Zigong argillaceous siltstones) with different weathering degree is selected as an example to study the water-softening property and the influence of degree of weathering. A series of mechanical and microstructure tests are carried out to analyze the weathering characteristics and mechanism of the Zigong argillaceous siltstones. The results of mechanical experiments reveal that the water content and the weathering degree of rock specimens both have a weakening effect on the compressive and shear strengths. According to the results of present microstructure tests, the mechanical properties of the Zigong argillaceous siltstones are closely correlated with their physical properties, including internal microstructure and material composition for highly weathered rocks or moderately weathered rocks (in both natural and saturation conditions). Finally, experimental results indicate that the changes of microstructure and internal materials are two main factors that influence rock strength parameters after contacting with water and that these properties reflect the rock weathering degree. In a word, when red-bed soft rocks are encountered in geotechnical engineering, special attention should be paid to presence of water.